Mitigation of swine pathogens in feed and feed manufacturing systems - Harrison, Olivia Lynn (Kansas State University, 2024)
Contaminated fomites such as feed, vehicles, and worker clothing increase the risk pathogen transmission within and between farms as feed mills. Maintaining prevention-based biosecurity practices and implementing mitigation as needed can reduce the risk of pathogen transmission through feed mills and potentially contaminated feed. Chemical disinfectants and mitigants have frequently been evaluated in laboratory settings but evaluating these products in commercial-like settings have been limited. A literature review was conducted to understand the link between Salmonella enterica 4,[5],12:i:- (STM) contaminated feed and pork products and human Salmonella outbreaks. The STM stain has been detected in swine farms, feed mills, swine feed, and in pork products themselves which suggest a link between the samples identified in the pork supply chain and foodborne illness in humans. However, the causal link between STM contamination in swine feed and STM cases in the human population has not been fully elucidated and is in need of continued research. Chapter 2 evaluates the efficacy of boot baths as a preventative biosecurity measure using either the control (no disinfection), liquid disinfectant, or dry powdered disinfectant on boots inoculated with porcine epidemic diarrhea virus (PEDV) and porcine reproductive and respiratory syndrome virus (PRRSV). Overall, the boot bath with dry powder was the most efficacious in reducing the detectable viral RNA on both boots and subsequent surfaces. In chapter 3, a data analysis of imported non-animal origin feed ingredients was conducted as the United States Department of Agriculture (USDA) categorizes the risk of African swine fever virus (ASFV) entry into the United States through these ingredients as “negligible to moderate, with high uncertainty”. As regulators and industry consider a potential pathway forward, the objective of this manuscript is to describe a process to determine if a voluntary or regulatory import policy is warranted by the United States. In 2020, soybean co- products and unprocessed grains and oilseeds from ASFV-positive countries represented 3.1% of all ingredients imported into the United States. Industry representatives from Canada and Australia, both countries which have policies in place to prevent ASFV entry, consistently stated their policies would not be feasible in the United States due to the differences in cost and complexity of the swine and feed industries. Overall, unprocessed grains and oilseeds and their co-products from ASFV positive countries represent a low percentage of imported ingredients into the United States; however, cautionary procedures may still be warranted given industry demand. A series of experiments were conducted in Chapter 4-6 to evaluate mitigation and disinfection strategies to reduce PEDV, PRRSV, and Seneca Valley virus 1 (SVV1) presence if feed, and subsequently the feed mill, were to become contaminated. The objectives of the experiments included 1) the use of flush batches to reduce viral presence, 2) pelleting as a thermal processing method, and 3) physical cleaning and decontamination strategies to disinfect feed manufacturing equipment. Samples were collected during each experiment and were analyzed via PCR for the quantity of detectable RNA and via a swine bioassay to determine viral infectivity. In Experiment 1, the use of formaldehyde as a chemical mitigant and the implementation of a flush batch reduced the quantity of viral RNA for PEDV, PRRSV, and SVV1; however, viral presence was still observed in feed and the dust on non-feed contact surfaces which could pose as a source of contamination if re-introduced into finished feed. Overall, pelleting reduced the quantity of detectable viral RNA and reduced the risk of infectivity in Experiment 2; however, small quantities of viral RNA remaining in the feed and environment following pelleting may increase the risk of re-contamination. In Experiment 3, complete facility decontamination (removal of organic matter with heated pressure washing, disinfection with 1% Virkon, disinfection with 5% household bleach, environmental heat held at 140°F for 48 hours) was the only decontamination treatment where PEDV, PRRSV, and SVV1 RNA was non-detectable after completion of all steps. Chlorine dioxide and heat treatments reduced the detectable quantity of RNA, but viral particles were still detectable across mill surfaces. During the bioassay, SVV1 and PEDV replication was not observed in pigs inoculated with samples from any experiment; however, PRRSV replication was noticed across multiple mitigation and decontamination treatments. At this time, it is unclear whether the observed PRRSV replication was due to cross-contamination or if infectious PRRSV RNA was capable of surviving undetected by PCR in the collected samples. Overall, feed mitigation using either flushes or thermal processing and feed mill decontamination strategies were able to reduce the overall presence of viral RNA and demonstrated the ability to reduce the risk of viral infection.
Keywords: Feed; Feed mills; Swine; Pathogens